Naringenin Regulates FKBP4/NR3C1/NRF2 Axis in Autophagy and Proliferation of Breast Cancer and Differentiation and Maturation of Dendritic Cell - Xiong, Hanchu; Chen, Zihan; Lin, Baihua; Xie, Bojian; Liu, Xiaozhen; Chen, Cong; Li, Zhaoqing; Jia, Yunlu; Wu, Zhuazhua; Yang, Min; Jia, Yongshi; Wang, Linbo; et al. (Frontiers in Immunology, 2022)
NRF2 is an important regulatory transcription factor involved in tumor immunity and tumorigenesis. In this study, we firstly identified that FKBP4/NR3C1 axis was a novel negative regulator of NRF2 in human breast cancer (BC) cells. The effect of FKBP4 appeared to be at protein level of NRF2 since it could not suppress the expression of NRF2 at mRNA level. Bioinformatics analysis and in vitro experiments further demonstrated that FKBP4 regulated NRF2 via regulating nuclear translocation of NR3C1. We then reported that naringenin, a flavonoid, widely distributed in citrus and tomato, could suppress autophagy and proliferation of BC cells through FKBP4/NR3C1/NRF2 signaling pathway in vitro and in vivo. Naringenin was also found to promote dendritic cell (DC) differentiation and maturation through FKBP4/NR3C1/NRF2 axis. Therefore, our study found that naringenin could induce inhibition of autophagy and cell proliferation in BC cells and enhance DC differentiation and maturation, at least in part, though regulation of FKBP4/NR3C1/NRF2 signaling pathway. Identification of FKBP4/NR3C1/NRF2 axis would provide insights for novel anti-tumor strategy against BC among tumor microenvironment.